Hand rearing a Linné's two‐toed sloth Choloepus didactylus at ZSL London Zoo. Issue 1 (24th July 2019) - Kelleher, K.‐A.; Ferguson, A.
Abstract : There is an increasing emphasis on the importance of ensuring the long‐term viability of taxa maintained in zoological collections. The captive population of Linné's two‐toed sloth Choloepus didactylus is monitored and managed in European and American breeding programmes. However, although breeding success is increasing the population is still not sustainable. Hand rearing is one option in the 'toolbox' of measures that can be used to assist with achieving integrated conservation goals, despite being challenging and labour intensive. This paper describes the enforced, but successful, hand rearing of a two‐toed sloth from 26 days of age at ZSL London Zoo, UK. The feeding protocol, behaviour and development are reported, and growth‐rate data are presented. While presenting data for only one individual, the experience has provided practical information about hand‐rearing practice that may inform future interventions in the management of ex situ populations, and assist with rescue and rehabilitation efforts for this and related species in the field. This species is classified as Least Concern by the International Union for Conservation of Nature and Natural Resources (IUCN) Red List; however, these sloths are threatened by habitat loss. Two of the six extant species of sloths are assessed as threatened; Pygmy three‐toed sloth Bradypus pygmaeus (Critically Endangered) and the Maned three‐toed sloth Bradypus torquatus (Vulnerable). Abstract : This paper describes the enforced, but successful, hand rearing of a Linné's two‐toed sloth Choloepus didactylus from 26 days of age at ZSL London Zoo, UK. The feeding protocol, behaviour and development are reported, and growth‐rate data are presented. This practical information may inform future interventions in the management of ex situ populations, and assist with rescue and rehabilitation efforts for this and related species in the field. (Photo: ZSL London Zoo)